2006
DOI: 10.1111/j.1440-1754.2006.00901.x
|View full text |Cite
|
Sign up to set email alerts
|

Methimazole‐induced toxic epidermal necrolysis in a 12‐year‐old girl

Abstract: Abstract:We report a 12-year-old girl with hyperthyreosis who presented methamazole-induced toxic epidermal necrolysis (TEN). The patient's past history suggests a presence of autoimmune disease. To our knowledge it is the first report describing such an adverse effect of methimazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…Toxic epidermal necrolysis has been also described in a 12-year-old-girl with hyperthyroidism treated with MMI. 15 Various cases of methimazole-induced hypersensitivity syndrome and immunologic side effects were reported, although the precise mechanisms were not elucidated. [16][17][18] An observational clinical study showed that nearly 20% of 100 children treated with MMI developed adverse effects, mainly skin eruptions and arthralgia.…”
Section: Discussionmentioning
confidence: 99%
“…Toxic epidermal necrolysis has been also described in a 12-year-old-girl with hyperthyroidism treated with MMI. 15 Various cases of methimazole-induced hypersensitivity syndrome and immunologic side effects were reported, although the precise mechanisms were not elucidated. [16][17][18] An observational clinical study showed that nearly 20% of 100 children treated with MMI developed adverse effects, mainly skin eruptions and arthralgia.…”
Section: Discussionmentioning
confidence: 99%
“…Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are severe skin and mucous membrane reactions often associated with medication use [5]. While there have been no prior reports of SJS/TEN linked to preoperative iodine solutions, there have been four documented cases of these conditions resulting from methimazole therapy in pediatric patients [6,7]. Notably, in those instances, the patients were actively taking methimazole when SJS/TEN developed [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…While there have been no prior reports of SJS/TEN linked to preoperative iodine solutions, there have been four documented cases of these conditions resulting from methimazole therapy in pediatric patients [6,7]. Notably, in those instances, the patients were actively taking methimazole when SJS/TEN developed [6,7].…”
Section: Introductionmentioning
confidence: 99%